2006
DOI: 10.3349/ymj.2006.47.6.811
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Estrogen Receptors in Hepatocellular Carcinoma in Korean Patients

Abstract: Expression of estrogen receptors (ER)-α and -β, as well as androgen receptor (AR), in hepatocellular carcinoma (HCC) is thought to be correlated with prognosis, survival, and male prevalence of HCC. These hypotheses are based on investigations of European patients; however the expression patterns of these receptors in Asian patients are largely unknown. In this study, we collected liver carcinoma and peritumor tissues from 32 patients (9 females and 23 males) in South Korea. The expression of ERs and ARs was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…Tavian et al [71] found higher AR mRNA levels in tumor than in the corresponding peri-tumoral tissue in a relatively small percentage of HCC samples, suggesting that AR mRNA levels are associated with the histological tumor differentiation showing a lower AR expression in poorlydifferentiated HCC than in well-differentiated tumors. In contrast, AR levels in Korean population with HCC do not show differences between tumor and peri-tumor tissues using RT-PCR [52] . Due to these conflicting reports on AR expression in HCC, there is a need for detailed investigation of AR mRNA as well as protein levels using more sensitive and accurate detecting quantitative methods.…”
Section: Androgen Receptormentioning
confidence: 72%
See 3 more Smart Citations
“…Tavian et al [71] found higher AR mRNA levels in tumor than in the corresponding peri-tumoral tissue in a relatively small percentage of HCC samples, suggesting that AR mRNA levels are associated with the histological tumor differentiation showing a lower AR expression in poorlydifferentiated HCC than in well-differentiated tumors. In contrast, AR levels in Korean population with HCC do not show differences between tumor and peri-tumor tissues using RT-PCR [52] . Due to these conflicting reports on AR expression in HCC, there is a need for detailed investigation of AR mRNA as well as protein levels using more sensitive and accurate detecting quantitative methods.…”
Section: Androgen Receptormentioning
confidence: 72%
“…Table 2 gives the details of these studies [18,19,40,45,51,52] . In situ hybridization using ER specific oligonucleotide sequence probe revealed that 11 out of 15 HCC tissue samples expressed ER mRNA [40] .…”
Section: Estrogen Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…There are several reports concerning the expression of AR mRNA and AR protein in tumor and in non-tumor parts of liver, suggesting that AR plays an important role in hepatocarcinogenesis [6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%